Valores pessoais e participação em projetos sociais, no contexto da responsabilidade social - Firmeza, Júlia de Souza (2007)
The theme social responsibility of organizations has had great projection nowadays. The companies that are considered socially responsible, among other actions, encourage voluntary work, encouragement that can vary from informal support, so that people can be volunteers out of timetable work; to the creation of formal programs of the company, in which the workers are invited to participate, using the normal time of working hours or other organizational resources. The workers’ participation, however, is still reduced in social projects that the companies develop. So, it is understandable that the personal values direct and guide the human behaviour and this research aims to verify the relation between personal values and the participation in social projects, supposing that the behavior of social participation is directly related to collective and mixed values. Thus, the research searched, supported by authors such as: Karkotli and Aragão and Melo Neto and Froes (in the social responsibility field) Schwartz and Tamayo (concerning to values) and Bordenave and Arango (in the participation theme) and through its objectives, first to describe the social projects of the company researched, then, to identify the type and level of participation of its workers and to identify also the axiological priority of the participants of the social projects of the company. The research was through quantitative and qualitative nature, and by exploratory and descriptive feature. The investigation occurred by means of a case study in a business as of city transportation as of passengers that is notable by its social responsibility. The results related to the first specific aim become evident that the researched organization, through its actions of social responsibility, gives spaces of social participation for its workers. Concerning the workers’ participation, the data show that the company still has a reduced number of participants, although, they have a voluntary and conscious participation of their contributions in social matters. As for personal values related to participation in social projects, in a group of researched subjects, it was got as a result, the presence of values of collective interests, such as, conformity and benevolence, and the value of universalism, characterized by individual and collective interests.